STUDI KUALITATIF STIGMA KELUARGA PENYINTAS COVID-19 DI WILAYAH RW 07 KELURAHAN POLEHAN - Shelia Umairoh Laidayana; Tri Nataliswati; Joko Wiyono (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
The Covid-19 pandemic has caused social impacts, one of which is stigma and changes to the Indonesian nation. Based on the phenomenon of the stigma of the family of Covid-19 survivors arising from being ostracized and feeling shunned by the community and a bad assessment of hospitals and health workers. This study aims to describe the stigma of the families of Covid-19 survivors. The design used in this research is qualitative with a phenomenological approach. Data collection was carried out by in-depth interviews where the results of the interviews were analyzed to find the theme. Based on the results of interviews with six informants, 9 themes were obtained, namely family experiences when exposed to covid, family feelings, healing process, response to the surrounding environment, impact, community understanding and application of health protocols, wisdom and hopes of Covid-19 survivors. Among them are experiences when exposed to covid-19, experiences of being rejected by hospitals, negative responses from the surrounding environment, namely being shunned and feared, the impacts that occur are social, economic, psychological and health impacts. People still think that the pandemic is a hoax and a trick. It is hoped that medical personnel, local health centers and community leaders provide education to Covid-19 survivors and for the community to read and filter the truth of information related to Covid-19.